Influence of the Fatty Acid Metabolism on the Mode of Action of a Cisplatin(IV) Complex with Phenylbutyrate as Axial Ligands - Theresa Mendrina; Isabella Poetsch; Hemma Schueffl; Dina Baier; Christine Pirker; Alexander Ries; Bernhard K. Keppler; Christian R. Kowol; Dan Gibson; Michael Grusch; Walter Berger; Petra Heffeter (MDPI AG, 2023)
For a variety of cancer types, platinum compounds are still among the best treatment options. However, their application is limited by side effects and drug resistance. Consequently, multi-targeted platinum(IV) prodrugs that target specific traits of the malignant tissue are interesting new candidates. Recently, cisPt(PhB)2 was synthesized which, upon reduction in the malignant tissue, releases phenylbutyrate (PhB), a metabolically active fatty acid analog, in addition to cisplatin. In this study, we in-depth investigated the anticancer properties of this new complex in cell culture and in mouse allograft experiments. CisPt(PhB)2 showed a distinctly improved anticancer activity compared to cisplatin as well as to PhB alone and was able to overcome various frequently occurring drug resistance mechanisms. Furthermore, we observed that differences in the cellular fatty acid metabolism and mitochondrial activity distinctly impacted the drug's mode of action. Subsequent analyses revealed that "Warburg-like" cells, which are characterized by deficient mitochondrial function and fatty acid catabolism, are less capable of coping with cisPt(PhB)2 leading to rapid induction of a non-apoptotic form of cell death. Summarizing, cisPt(PhB)2 is a new orally applicable platinum(IV) prodrug with promising activity especially against cisplatin-resistant cancer cells with "Warburg-like" properties.